Apraxia: a complexa relação entre corpo e linguagem - Catrini, Melissa (2011)
This study was triggered by clinical questions related to the problem of Apraxia. When there is incontestable neurological disease, any articulation disorder is immediately assumed and labeled as a Speech Apraxia or Dysarthria (CRARY,1993) even if an organic damage cannot be effectively confirmed by medical diagnosis or technological devices. The fact is that clinical avaliation tends to follow the same direction: the neurological damage is not detectable, but does it exist! Under such a situation, the suspicion falls on Apraxia of Speech, a pathology usually defined as a motor speech disorder observable in articulatory and prosodic difficulties without muscle damage. Therefore, a question can be raised: what causes that articulatory (functional) symptom? . Apraxia affects the body and the body is, according to the medical viewpoint an object of physiology and pathology. I endeavoured to indicate and justify the strength of that theoretical and clinical discourse, which sustains itself on the philosophical dichotomic opposition between mind and body, i.e., between cognition and organism. Apraxia is, thus, traditionally approached, studied and defined through that perspective. In the present study, Freud is taken as a landmark because he introduced a completely different trend of reasoning which dissolves the philosophical and psychophysical dualism mindbody. Affected by the wreckage of hysteria and the holes of aphasia, he could be state that structure and body functions do not go side by side and a new and revolutionary conception of the body could be introduced and developed in studies of Apraxia the human body is bodylanguage. This thesis tried to follow Freud s theoretical direction concerning the relationship between body and language, this study is conducted in accordance with the reflections on languare pathology and clinic developed within the research group Language acquisition, pathology and clinic, coordinated by Lier-DeVitto and Arantes, at LAEL /PUCSP